Himalayan rock slope stability investigation using empirical and numerical approach along NH-44 of Jammu and Kashmir, India - Jaiswal A.; Verma A.K.; Pandit B.; Singh T.N. (My University, 2025)
Slope instability is a complex geological phenomenon triggered by heavy rainfall, earthquakes, tectonic forces and anthropogenic activities. Unplanned excavation of rock slopes for the development and maintenance of infrastructure such as highways, railways, and buildings in hilly regions plays a significant role in causing slope instability. The present work conducts a comprehensive stability assessment of rock slopes along the national highway (NH-44) section of the Ramban district of Jammu and Kashmir. The kinematic investigation was carried out to determine the different modes of failure of road-cut slopes, and two main modes were found: planar and wedge. Various empirical classifications have been applied for the assessment of slope stability, like geological strength index (GSI), slope mass rating (SMR), Chinese slope mass rating (CSMR), and continuous slope mass rating (CoSMR). Numerical analysis through universal distinct element code (UDEC) has been conducted to evaluate the stability of four critical rock slopes under static and dynamic loading conditions. Modelling results have provided insights into the failure mechanism, and based on these findings, remedial measures have been proposed. Three (L-1, L-3, and L-13) out of four slopes were determined to be unstable under static conditions, with factors of safety (FoS) < 1.2 and under dynamic conditions, two slopes were unstable with FoS < 1.0. However, one (L-8) slope was found to be stable under both static and dynamic conditions, with FoS 1.29 and 1.12, respectively. Installing rock bolts reduced displacement for slopes L-1 and L-13, with reductions of 11.86% and 21.05% under static conditions and 4.09% and 18.75% under dynamic conditions, respectively, while L-3 does not stabilise even after installation of rock bolts. © Indian Academy of Sciences 2024.